Neuroanatomical correlations of visuospatial processing in primary progressive aphasia. Issue 2 (14th March 2022) - Tee, Boon Lead; Watson Pereira, Christa; Lukic, Sladjana; Bajorek, Lynn P.; Allen, Isabel Elaine; Miller, Zachary A.; Casaletto, Kaitlin B.; Miller, Bruce L.; Gorno-Tempini, Maria Luisa
Abstract: Clinical phenotyping of primary progressive aphasia has largely focused on speech and language presentations, leaving other cognitive domains under-examined. This study investigated the diagnostic utility of visuospatial profiles and examined their neural basis among the three main primary progressive aphasia variants. We studied the neuropsychological performances of 118 primary progressive aphasia participants and 30 cognitively normal controls, across 11 measures of visuospatial cognition, and investigated their neural correlates via voxel-based morphometry analysis using visuospatial composite scores derived from principal component analysis. The principal component analysis identified three main factors: visuospatial-executive, visuospatial-memory and visuomotor components. Logopenic variant primary progressive aphasia performed significantly worst across all components; nonfluent/agrammatic variant primary progressive aphasia showed deficits in the visuospatial-executive and visuomotor components compared with controls; and the semantic variant primary progressive aphasia scored significantly lower than nonfluent/agrammatic variant primary progressive aphasia and control in the visuospatial-memory component. Grey matter volumes over the right parieto-occipital cortices correlated with visuospatial-executive performance; volumetric changes in the right anterior parahippocampal gyrus and amygdala were associated with visuospatial-memory function, and visuomotor composite scores correlated significantly with the grey matter volume at the right precentral gyrus. Discriminant function analysis identified three visuospatial measures: Visual Object and Space Perception and Benson figure copy and recall test, which classified 79.7% (94/118) of primary progressive aphasia into their specific variant. This study shows that each primary progressive aphasia variant also carries a distinctive visuospatial cognitive profile that corresponds with grey matter volumetric changes and in turn can be largely represented by their performance on the visuomotor, visuospatial-memory and executive functions. Abstract : The three canonical variants of a primary progressive aphasia (PPA) carry different visuospatial cognitive profiles. Tee et al. demonstrate that the distinct visuospatial cognitive phenotypes are associated with anatomical changes over the right hemisphere, albeit the structural changes of PPA are most evident over the left hemisphere. Graphical Abstract: Graphical Abstract